I will take a nap! - Willems, Mo (New York : Hyperion Books for Children, 2015)
Gerald is tired and cranky and wants to take a nap, but Piggie is not helping.
Keywords: Naps (Sleep) -- Juvenile fiction; Elephants -- Juvenile fiction; Swine -- Juvenile fiction; Friendship -- Juvenile fiction